2007
DOI: 10.1016/j.combustflame.2006.12.012
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of flame edges in diffusion-flame/vortex interactions

Abstract: We analyze the local flame extinction and reignition of a counterflow diffusion flame perturbed by a laminar vortex ring. Local flame extinction leads to the appearance of flame edges separating the burning and extinguished regions of the distorted mixing layer. The dynamics of these edges is modeled based on previous numerical results, with heat release effects fully taken into account, which provide the propagation velocity of triple and edge flames in terms of the upstream unperturbed value of the scalar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Equation (8b) shows that the modified Damköhler number at the extinction strain rate reduces for large values of the Lf number, implying that a spray flame extinguishes for smaller strain rates compared to a gaseous flame as found in [26]. In [27], the front propagation velocity U F for purely gaseous flames is observed to be a function of the Damköhler number, which presents an asymptotic value. This behavior is here also assumed for spray flames:…”
Section: Spray Flame Characterization and Assumptionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Equation (8b) shows that the modified Damköhler number at the extinction strain rate reduces for large values of the Lf number, implying that a spray flame extinguishes for smaller strain rates compared to a gaseous flame as found in [26]. In [27], the front propagation velocity U F for purely gaseous flames is observed to be a function of the Damköhler number, which presents an asymptotic value. This behavior is here also assumed for spray flames:…”
Section: Spray Flame Characterization and Assumptionsmentioning
confidence: 93%
“…In the following, this spectral diagram is verified through numerical simulations. It is noted that a complete characterization of the reignition phenomenon will require an extensive study on edge spray flames, in analogy with the work of Hermanns et al [27] for gaseous flames. This, however, is beyond the scope of this study.…”
Section: Spray Spectral Diagrammentioning
confidence: 99%
“…According to the analysis of a diffusion jet flame, the mixing is approached via vortex roll-up [30,31]. On the other hand, the corresponding strain effects of vortices have also been investigated [30][31][32][33]. Accordingly, the connections between vortices and the ignition/flame spread of the present study are expected to be significant.…”
Section: Introductionmentioning
confidence: 93%
“…15,19,20 The direct-numerical-simulation ͑DNS͒ study of Sripakagorn et al 18 in reacting isotropic turbulence employing a singlestep kinetic model revealed three modes of reignition: an independent-flamelet scenario, where the extinguished flamelets reignite through autoignition, an edge-flame propagation scenario, where reignition occurs through propagation of edge flames, which are extremities of diffusion flame holes, 21 and an engulfment scenario, where turbulent convection of hot products from neighboring burning regions leads to reignition. Sripakagorn et al 18 reported that when the excursions of over e are relatively large, reignition is likely to occur through edge-flame propagation and engulfment scenarios.…”
Section: Recent Experimentsmentioning
confidence: 99%
“…Details of the vortex implementation may be found in Ref. 19. We employ a single-step kinetic model 15 for n-heptane oxidation, i.e.,…”
Section: Numerical Formulationmentioning
confidence: 99%